Extraversion, Neuroticism, and Employee Voice: A Conservation of Resources Perspective - Li, Jia; Xu, Sen (Frontiers in Psychology, 2020)
Drawing on the Conservation of Resources (COR) theory, we constructed a model about how two of Big-Five personality traits, extraversion and neuroticism, respectively, influence employee voice through an indirect effect of emotional exhaustion. We distributed two wave surveys to 435 employees and their supervisors in a Chinese state-owned bank. Our analyses indicated that extraversion had a positive indirect effect on employee voice via emotional exhaustion, whereas neuroticism had a negative indirect effect on employee voice via emotional exhaustion. We concluded by discussing our theoretical implications with research on employee voice and COR. Additionally, we discussed our practical implications for managerial practices and for the general public.